Home Sweet Houseplant : A Room-by-Room Guide to Plant Decor - Chapman, Baylor; Pick, Aubrie (New York : Artisan A division of Workman Publishing Co., Inc., 2021)
The complete guide to adding plant life to your spaces, with ideas and inspiration for adding plants to every room in your home.
Includes index.
Keywords: House plants; House plants in interior decoration; Indoor gardening